Tunnug 1 (Arzhan 0) – an early Scythian kurgan in Tuva Republic, Russia. (September 2018) - Caspari, Gino; Sadykov, Timur; Blochin, Jegor; Hajdas, Irka
Abstract: The burial mound Tunnug 1 (Arzhan 0) lies in a swamp of the Uyuk River Valley, Tuva Republic, Russia. The construction of this princely Scythian tomb is similar to the earliest identified Scythian kurgan Arzhan 1. Preserved wood from the burial mound was dated through AMS to the 9th century BCE. This confirms that Tunnug 1 (Arzhan 0) belongs to the oldest Scythian cultural horizon and potentially predates Arzhan 1. Due to its peculiar topographic location Tunnug 1 (Arzhan 0) appears to be a frozen tomb.